Essays on public health in developing countries / Tey Nai Peng - Tey, Nai Peng (2017)
Reproductive health is a crucial part of general health and a central feature of human development. Since gaining global attention at the 1994 International Conference on Population and Development (ICPD), the importance of reproductive was reaffirmed as one of the eight goals of Millennium Development Goals (MDGs), and in the post-2015 development agenda. This thesis addresses the key issues of public health affecting childbearing women and the older people. Universal access to reproductive health, reducing maternal deaths and non-communicable diseases (NCDs) are among the main targets of the new agenda for the global Sustainable Development Goals (SDGs) 2015- 2030. The objectives of the thesis are: 1. To investigate problems relating to reproductive health and NCDs, 2. To examine the correlates and risk factors of reproductive health outcomes and NCDs that are of public health concerns, 3. To evaluate the barriers to the utilization of health services in the developing countries, and 4. To put forth recommendations for policy and research. The objectives are partially achieved through the writing of five essays listed below. A comprehensive review of the literature was carried out to complete the thesis. 1. Proximate Determinants of Fertility in Peninsular Malaysia 2. Medical Students’ Attitudes toward Abortion Education: Malaysian Perspectives 3. Correlates of and Barriers to the Utilization of Health Services for Delivery in South Asia and sub-Saharan Africa 4. Ethnic and Gender Differentials in Non-communicable Diseases and Self-rated Health in Malaysia 5. The Debilitating Effects of Chronic Diseases among the Oldest Old in China An analysis of the proximate determinants of fertility indicate that marriage postponement and contraceptive use are the two most important factors affecting fertility, but breastfeeding and abortion also play a role in fertility reduction. Abortion is a serious public health issue, and it poses high risks to the health and life of women. A survey on medical students in Malaysia showed that 9 out of 10 students wanted more training on the general knowledge and legal aspects of abortion, and pre- and post-abortion counseling. Hence, there is a need to incorporate abortion education in the curriculum of medical schools. Unmet need for contraception remains at a high level in some developing countries. The reproductive health needs of couples and adolescents need to be given more attention. The national family planning program needs to be revitalized to provide services beyond family planning such as infertility treatment and bio-medical research. A family policy is also needed to foster family development and to advocate for family friendly work environment for work-life balance. Chronic diseases are rising rapidly, affecting people of all ages, especially the older people. Preventive, protective and rehabilitative measures must be taken to reduce these diseases. The root cause of the chronic diseases, including modifiable factors such as unhealthy life style and diet must be addressed. There exists wide gaps in the utilization of health services. Efforts must be made to overcome supply-side and demand-side barriers. The thesis concludes by putting forth some recommendations for policy and future research.